Optimalisasi Pelayanan Kesehatan Remaja Putri Melalui Pemeriksaan dan Edukasi tentang Kesehatan Reproduksi Remaja: Optimizing Health Services for Adolescent Girls Through Screening and Reproductive Health Education - Greiny Arisani; Gunarmi Gunarmi; Siti Fadhilah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
One of the most prominent issues among adolescents is reproductive health. This is closely related to biological changes and the maturation of reproductive organs, as well as preparing adolescents for the next stage of development, namely reproduction. One strategy with the potential to have a significant impact is the promotion of health among adolescent girls, which includes health education and health screening. This community service activity was implemented using a persuasive and educational approach, including reproductive health education through booklet media, peer group discussions, and health examinations involving 30 adolescent girls. The results showed an increase in knowledge among adolescent girls, as indicated by an improvement in the average knowledge score from 56.33 before the intervention to 88.67 after the intervention. This finding indicates that reproductive health education delivered through booklet media and peer group discussions is effective in improving adolescent girls’ understanding of adolescent reproductive health. Furthermore, the results of the health examination revealed that although most participants were not anemic and had normal nutritional status, some still experienced mild to moderate anemia. In addition, variations in body mass index were identified, including underweight, overweight, and obesity, as well as a risk of chronic energy deficiency (CED) among some participants. These findings indicate that nutritional problems and anemia among adolescent girls remain a concern and require continuous prevention and management efforts. Therefore, integrating health education and adolescent health services in schools is expected to be an effective, sustainable intervention model for improving the health status of adolescent girls.